Converting Workforce Diversity into an Advantage for the Organization - Mehta , Jyotsna Diwan (Gyan Management Journal, 2008)
This article proposes to e plore not only the conceptual approach to people diversity at the workplace but also attempts to create a model for understanding and managing diversity. For this we will analyze why diversity occurs in organizations and then go on to explore the key drivers of workforce diversity .The phenome_non of diversity is on the increase so we will try to identify what are the reasons for this increase. Diversity has a deep impact upon the processes of the organizations. If we manage diversity well it will result in positive outcomes for the organization but if we are unabl
Keywords: Workforce Diversity; Advantage; Organization